Randomised trial of unselected BRCA testing in ashkenazi jews: long term outcomes and factors affecting uptake of testing. (1st November 2019) - Manchanda, R; Burnell, M; Gaba, F; Desai, R; Wardle, J; Gessler, S; Side, L; Sanderson, S; Loggenberg, K; Brady, A; Dorkins, H; Wallis, Y; et al.
Abstract : Introduction/Background: Unselected population-based BRCA -testing enables application of genomics on a population-scale to maximise primary-prevention for breast-&-ovarian cancer. We present factors affecting uptake and long-term follow-up results of the GCaPPS-trial comparing population-based and Family-History (FH)/Clinical-criteria based BRCA -testing. Methodology: Design: Randomised-Controlled-Trial (ISRCTN73338115 ) GCaPPS, with two-arms: (a)Population-Screening (PS); (b)FH/Clinical-criteria based testing. Setting: North-London Ashkenazi-Jewish(AJ) population. Population-based RCT (1:1). Participants recruited through self-referral, from North-London AJ-population. Inclusion-criteria: AJ women/men >18years. Exclusion-criteria: prior BRCA -testing or first-degree-relatives of BRCA -carriers. Interventions: Pre-test counselling for BRCA-testing through recruitment-clinics (clusters). Genetic-testing for Jewish BRCA founder-mutations: 185delAG(c.68_69delAG), 5382insC(c.5266dupC) and 6174delT(c.5946delT), for (a)all participants in PS-arm; (b)those fulfilling FH/clinical-criteria in FH-arm. Validated questionnaires (HADS/MICRA/HAI/SF12) analysed psychological well-being/quality-of-life outcomes at baseline, 1-year, 2-years and 3-years follow-up. Linear mixed-models and appropriate contrast-tests analysed the impact of BRCA -testing on psychological and quality-of-life outcomes over 3-years. Socio-demographic/family-history/knowledge/psychological well-being data along-with benefits/risks/cultural-influences (18-item-questionnaire measuring 'attitude') were collected. Logistic-regression models evaluated factors affecting uptake/interest/intention-to undergo BRCA -testing. Results: 1034 (women=691/men=343) participants randomized to PS (n=530) or FH (n=504) arms. There was a statistically significant decrease in anxiety(p=0.046) and total anxiety-&-depression scores(p=0.0.012) in the PS-arm compared to FH-arm over 3years. No significant difference was observed between FH/PS arms for depression, health-anxiety, distress, uncertainty, quality-of-life or experience scores associated with BRCA-testing. 18/30(60%) BRCA -carriers identified did not fulfil BRCA -testing clinical-criteria. The total BRCA-prevalence= 2.9%(CI:1.97%, 4.12%) (BRCA1=1.55%(CI:0.89%, 2.5%); BRCA2=1.35%(CI:0.74%, 2.26%)). The BRCA-testing uptake was 88%. Being married/cohabiting had four-fold higher-odds for BRCA -testing uptake(p=0.009). Reduced uncertainty/reassurance were the most important factors affecting decision-making. Increased importance/concern towards risks/limitations (confidentiality/insurance/emotional-impact/inability to prevent cancer/marriage-ability/ethnic-focus/stigmatization) were significantly associated with lower-odds of undergoing BRCA -testing, discriminating between acceptors and decliners. Conclusion: Population-based AJ BRCA- testing has high acceptability, doesn't adversely affect long-term psychological well-being or quality-of-life, decreases anxiety and could identify up-to 150% additional BRCA -carriers. Pre-test counselling increases awareness of disadvantages/limitations of BRCA -testing, influencing final cost-benefit perception and decision-making on undergoing testing. Disclosure: IJ and UM have a financial interest in Abcodia, Ltd., a company formed to develop academic and commercial development of biomarkers for screening and risk prediction. IJ is a member of the board of Abcodia Ltd, a Director of Women's Health Specialists Ltd and received consultancy from Beckton Dickinson. RM declares research funding from The Eve Appeal and Cancer Research UK into population testing and from Barts & the London Charity and Rose Trees Trust outside this work, an honorarium for grant review from Israel National Institute for Health Policy Research and honorarium for advisory board membership from Astrazeneca/MSD. RM is supported by an NHS Innovation Accelerator (NIA) Fellowship for population testing. The other authors declare no conflict of interest.